PENERAPAN KESEJAHTERAAN HEWAN PADA BEBERAPA PETERNAKAN AYAM RAS PEDAGING (STUDI KASUS DI KABUPATEN BANGKA - Susanti Susanti; Nur Annis Hidayati; Budi Afriyansyah (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2017)
Animal welfare is a less common issue in Bangka. Animal welfare is the well-being of animals. For several meat consumers, it is important to know how the farmed chicken raised. Bangka Regency has the highest number of broiler among other regencies in Bangka Belitung Province. Since its high population, chicken farm in Bangka Regency were studied as a case study of how animal welfare is applied in the Province. Aim of this research was to assess the level of animal welfare in five chicken farms in Bangka Regency. Data were collected through interview and observation, then were analysed by a modified Animal Needs Index (ANI) from Bartussek. Several animal welfare categories were movement, social interaction, quality flooring, light and air, and cleanliness. Results showed that ANI index were varied from 14.2 to 16.5, with an average is 16. According to the Animal Needs Index (ANI), a score of 16 to<21 indicates the quite sufficient of welfare.